Identifikasi Yuridis Sewa Kendaraan Bagi Wisatawan Asing Terhadap Upaya Pemulihan Pariwisata Bali Pasca Pandemi - Ariesta, I Putu Agus Suarsana; Asih, Anak Agung Ketut Sri (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2024)
The COVID-19 pandemic has a serious impact on the tourism industry throughout the world, including on Bali which is known as a major tourist destination. Juridical identification of vehicle rental regulations is important in post-pandemic tourism recovery efforts. This article aims to analyze legal framework regarding vehicle rental for foreign tourists in Bali, with a focus on aspects such as licensing, consumer protection, and the obligations of renters and service providers. Even though Bali has relaxed some tourist travel restrictions, new challenges have emerged regarding arranging vehicle rentals that are safe and in accordance with health protocols. It is necessary to pay attention to whether the existing regulations are sufficient to accommodate new post-pandemic needs. In addition, important to identify opportunities or obstacles that the vehicle rental industry may face in adapting. An in-depth understanding of the applicable legal framework can provide guidance for vehicle rental service providers and related agencies to take appropriate steps to facilitate tourism recovery in Bali. By ensuring compliance with legal regulations, as well as paying attention to health and safety needs, it is hoped that the vehicle rental industry can become one of the driving forces for tourism recovery in Bali after the pandemic.